2019
DOI: 10.1002/adom.201901053
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Stimulated Charge Transport in Bilayer Molecular Junctions for Photodetection

Abstract: Eleven bilayer molecular junctions (MJs) consisting of two different 5–7 nm thick molecular layers between conducting contacts are investigated to determine how orbital energies and optical absorbance spectra of the oligomers affect the photocurrent (PC) response, the direction of photoinduced charge transport, and maximum response wavelength. Photometric sensitivity of 2 mA W−1 and a detection limit of 11 pW are demonstrated for MJs, yielding an internal quantum efficiency of 0.14 electrons per absorbed photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 64 publications
3
34
0
Order By: Relevance
“…Many studies has been reported quite recently using diazonium electroreduction to graft conductive oligomers on surfaces [38,[43][44][45][46][47]. Ultrathin layers can be generated since the growth is limited by the conductivity of the organic layer in the potential range required for the electroreduction of the diazonium salt.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies has been reported quite recently using diazonium electroreduction to graft conductive oligomers on surfaces [38,[43][44][45][46][47]. Ultrathin layers can be generated since the growth is limited by the conductivity of the organic layer in the potential range required for the electroreduction of the diazonium salt.…”
Section: Introductionmentioning
confidence: 99%
“…The first type of MJ considered has the structure shown in Figure A, consisting of 4–100 nm oligomers of NAB between conducting carbon contacts, designated as Q/Cr 4 /Au 30 /eC 10 /NAB d /eC 10 /Au 20 , where subscripts indicate layer thickessess in nanometers, eC is electron beam deposited carbon derived from graphite rods as described in detail previously, , and Q is a quartz substrate to avoid silicon due to its photoactivity. A second type of MJ is a bilayer structure also previously reported to be photoactive, containing anthraquinone and tetraphenyl porphyrin oligomeric layers deposited from diazonium reagents. , The fabrication of junctions is detailed in Supporting Information section 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several examples of the interactions of light with MJs with d = 1–10 nm have been reported, as have several treatments of the relevant theory. Recent research on all-carbon molecular junctions reveals activationless, photoassisted transport across 4–60 nm of an aromatic oligomer illuminated by UV–vis light. , Figure C illustrates three modes of photon/MJ interactions which both absorb and emit light during electron transport across the molecular layer. Light absorption in the conducting contacts can excite electrons sufficiently to enter empty molecular orbitals (mode #1 Figure C), resulting in current flow at zero bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoelectronics is based on switching devices, and molecular electronics have tried to use various active molecules to develop resistive switches. Some approaches are based on redox-active molecules while others are based on photoactive systems, with few studies combining the two properties. In this context, photochromic molecules, i.e. molecules with two different forms (open/nonconjugated and closed/conjugated), which can be interconverted by light irradiation, have been widely used and incorporated into single-molecule and large-area Molecular Junctions (MJs). , Most studies are devoted to monolayers or single-molecule-based MJs where the dominant transport mechanism is direct tunneling.…”
mentioning
confidence: 99%